ACK1 condensates promote STAT5 signaling in lung squamous cell carcinoma - Andong Liu; Xia Lu; Yanyang Song; Jiaying Pei; Ruozheng Wei (Cancer Cell International)
Abstract Background ACK1, a non-receptor tyrosine kinase, phosphorylates various substrates involved in cancer progression. Its oncogenic activity is driven by gene amplification, mutations, and post-translational modifications. However, additional regulatory mechanisms that govern ACK1 activity remain to be fully understood. Liquid-liquid phase separation (LLPS) has emerged as a key mechanism of cellular compartmentalization, controlling the spatiotemporal dynamics of signaling pathways. Methods Expression plasmids and corresponding mutants were generated using molecular cloning techniques. Protein expression and localization were assessed through western blotting, immunofluorescence, and confocal microscopy. LLPS properties were evaluated using time-lapse imaging, photobleaching, optoDroplet assays, and in vitro droplet formation assays. Cellular functions were examined through colony formation and wound-healing assays. STAT5 signaling activation was assessed by western blotting, co-immunoprecipitation (Co-IP), immunofluorescence, RNA sequencing (RNA-Seq), and Gene Set Enrichment Analysis (GSEA). Results We demonstrate that ACK1 is frequently amplified and overexpressed in lung squamous cell carcinoma (LUSC). In LUSC cells, ACK1 undergoes LLPS, a process that depends on the intrinsically disordered region (IDR, 96–156 aa) but is independent of its kinase activity. We identify that the IDR induces droplet formation, with the 143–156 aa segment being essential for this activity. Furthermore, our data reveal that ACK1 phosphorylates STAT5 in LUSC cells. ACK1 condensates recruit the non-catalytic adaptors NCK1 and NCK2 and enhance STAT5 signaling. These condensates promote STAT5 nuclear localization and transcriptional activity, thereby facilitating LUSC cell growth and migration. Conclusions Our findings highlight the crucial role of ACK1 condensates in oncogenic STAT5 signaling and suggest that targeting the formation of ACK1 condensates could serve as a potential therapeutic strategy for LUSC.